Mapping Biological Materials Supporting the Implementation of the Project for Strengthening Pancasila Student Profiles - Istianah, Naila; Rusilowati, Ani; Ellianawati, Ellianawati (Unnes Science Education Journal, 2024)
The results of interviews conducted with the Chair of the Biology subject teachers deliberation in Cirebon Regency revealed that biology learning shows that the implementation of the independent learning curriculum in schools has been running, but teachers face several obstacles in its implementation. This is related to the lack of understanding of the nature of independent learning, the lecture method still dominates, difficulties in creating open modules and the incompatibility of the learning platform with what is in it. So that at the evaluation stage teachers experience difficulties in carrying out assessments. The research aims to map Biology material to support the implementation of the Strengthening Pancasila Student Profile (P5) Project in eight schools in Cirebon Regency, West Java, for Phase E and Phase F.  Using a qualitative descriptive method with a case study approach, this research analyzes the relationship between Biology material with theme P5, designing project-based learning designs, identifying teacher constraints, and formulating student engagement strategies. The research result showed  that in Phase E, the Ecosystems and Biotechnology materials were used by two schools (25%), while the Diversity of Living Creatures materials were used by one school (12.5%). In Phase F, Plant Growth and Development material was dominantly used by three schools (37.5%) with the theme Sustainable Lifestyle. Learning design involves applicable projects, such as making compost, biotechnology donuts, reforestation, and using waste to make fashion works. The main challenges are teacher competence (50%) in integrating material and determining project themes, as well as student interest (25%) and limited school facilities (12.5%). These findings emphasize the importance of increasing teacher competency and student engagement strategies to optimize the implementation of P5 with character and environmental insight.